Laparoscopic Sacrocolpopexy for Beginners : How to Start if you Never Dared Before? - von Theobald, Peter (Springer International Publishing : Imprint: Springer, 2017)
This book offers a practical surgical guide, helping surgeons learn the technique needed to perform Laparoscopic SacroColpoPexy (LSCP). To do so, it explains the surgical process in straightforward language, supplemented by images and diagrams, while also discussing why this procedure is so effective. The book has two primary goals: to provide those surgeons who have never performed LSCP before with essential insights and technical expertise, based on the author's 20 years of practical surgical experience; and to allay the common fear of possible complications. Following a 2012 FDA warning, surgeons whose work involved vaginal prolapse repair have been looking for an alternative technique. Though LSCP offers a safe alternative to current methods, the available literature on it is sparse. This book provides a comprehensive guide to the techniques and methods needed by surgeons operating on pelvic organ prolapse in a range of different specialties, including urogynecology, urology, and gynecology.
Keywords: Medicine.; Gynecology.; Surgery.; Urology.; elektronické knihy; electronic books